Differences of Effectiveness of Autogenic and Supportive Therapy on Post Traumatic Stress Disorder in Post Flood Elderly (Rengel Village, Rengel, Tuban District) - Karyo; Kusno Ferianto (Science Midwifery, 2020)
Post Traumatic Syndrome Disorder is a syndrome of anxiety, autonomic lability, and experiencing flashbacks of experiences that are very sad after physical or emotional stress that exceeds the limits of an ordinary person's endurance. Research Objectives To determine the difference between autogenic and supportive therapy for Post Traumatic Stress Disorder in post-flood victims in Rengel District, Tuban Regency. Method: Quasy experimental design with a prospective approach with a pretest-posttest design with control group. The sample used systematic random sampling totaling 60 respondents (30 respondents in the experimental group and 30 respondents in the control group). Data collection using a questionnaire. This study uses probability sampling techniques and is tested by the Sample t-Test (Independent sample t-Test). Results: The Wilcoxon test obtained p value 0.000 <0.05, which means that there is a difference in the effectiveness of autogenic and supportive therapy against Post Traumatic Stress Disorder in the Elderly Post Flood (in Rengel Village, Rengel District, Tuban Regency). Discussion: Providing Autogenic and Supporting Therapy can be an alternative therapy to relieve post-flood trauma. Suggestion: Autogenic and supportive therapy can be applied early after a disaster and is expected to reduce the number of trauma in the elderly.